Yttrium oxysulfide nanosized spherical particles doped with Yb and Er or Yb and Tm: efficient materials for up-converting phosphor technology field - Pires, Ana Maria [UNESP]; Serra, O. A.; Davolos, Marian Rosaly [UNESP] (Elsevier B.V., 2004)
This work reports on the preparation, structural and luminescent studies of nanosized up-converter phosphors Y2O2S:Yb(4%), Er(0.1%) and Y2O2S:Yb(4%), Tm(0.1%),both from polymeric and basic carbonate precursors. The precursors were submitted to a sulphuration process that was previously developed for oxysulfide preparation from basic carbonate. From XRD data, all phosphors presented the oxysulfide phase and the mean crystallite size estimated from the Scherrer formula in the range of 15-20 nm. Polymeric precursor leads to the smallest crystallite size independent on the doping ion. SEM and TEM results confirmed that basic carbonate leads to spherical particles with narrow size distribution and mean diameter of 150 nm, and polymeric precursor smaller spherical particles with diameter between 20 and 40 nm. Up-conversion studies under 980 nm laser excitation showed that Er-doped phosphors present strong green emission related to H-2(11/2), S-4(3/2) --> I-4(15/2) Er transitions as well as the red ones, F-4(9/2) --> I-4(15/2). Tm-doped samples show strong blue emission assigned to (1)G(4) --> H-3(6) and also the red ones, related to (1)G(4) --> F-3(4). Therefore, the sulphuration method was successfully applied to prepare nanosized and nanostructured blue and green up-converter oxysulfide phosphors starting from basic carbonate and polymeric precursors. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: up-conversion; UPT; spherical shape; rare earth ions; luminescence